Effectiveness of The International Class Learning Program For Students of SD Muhammadiyah 3 IKROM - Nuroh, Ermawati Zulikhatin; Tikasar, Berlian Ayu; Andini, Kharisma Putri; Ummah, Nazrotul; Savira, Salsabila Bulqis (Procedia of Social Sciences and Humanities, 2024)
The School Field Introduction Program is an assignment activity to students to implement learning outcomes through observation of the learning process in schools or educational institutions. The activity program aims to improve knowledge and expertise for students and provide teacher mentoring experience at the elementary school level and strengthen educational academic competencies for PGSD study program students. The research methodology used is observation, data collection techniques carried out through observation accompanied by various recordings of conditions and objects in the field. This program was carried out for 1 week at SD Muhammadiyah 3 Ikrom. The results obtained that in the school there is a special class, namely ICP (International Class Program), that students who are included in the learning program must pass a selection process. In the learning process students are accustomed to communicating using English and there are learning methods to make it easier for students to develop their ability to master the English language.